2013
DOI: 10.1519/jsc.0b013e3182578115
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Strongman Training on Salivary Testosterone Levels in a Sample of Trained Men

Abstract: Strongman exercises consist of multi-joint movements that incorporate large muscle mass groups and impose a substantial amount of neuromuscular stress. The purpose of this study was to examine salivary testosterone responses from 2 novel strongman training (ST) protocols in comparison with an established hypertrophic (H) protocol reported to acutely elevate testosterone levels. Sixteen men (24 ± 4.4 years, 181.2 ± 6.8 cm, and 95.3 ± 20.3 kg) volunteered to participate in this study. Subjects completed 3 protoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 31 publications
3
33
3
Order By: Relevance
“…RST has also been reported to induce large hormonal elevations with acute increases in testosterone (12,29,34) and cortisol (5,14,8). The reader is referred to a recent review on the physiology of strongman training in which direct comparsion between acute responses to strongman training sessions and traditional strength training sessions are elaborated (42).…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 2 more Smart Citations
“…RST has also been reported to induce large hormonal elevations with acute increases in testosterone (12,29,34) and cortisol (5,14,8). The reader is referred to a recent review on the physiology of strongman training in which direct comparsion between acute responses to strongman training sessions and traditional strength training sessions are elaborated (42).…”
Section: A C C E P T E Dmentioning
confidence: 99%
“…While research by Ghigiarelli et al (12) has examined the testosterone response to an entire ST session and compared it with that of hypertrophy training, no research has collectively examined the metabolic and hormonal effects of ST and compared it directly to RST. Therefore the aim of this study was to examine the acute metabolic and hormonal response to ST and compare it with RST in regards to overall session profile.…”
Section: A C C E P T E Dmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors reported recovery of spiked material for testosterone and cortisol was 80-94 % and 83-100 % respectively. Moreover, substantial differences existed between laboratories, as a result of traceability, clean-up procedures, or issues with calibration Crewther and colleagues [37] reported power trained males had mean basal sal-T concentrations of 107 pg · ml − 1 (371 pmol · L − 1 ) whereas Ghigiarelli et al [57] reported basal levels of as high as 180 pg · ml − 1 (624 pmol · L − 1 ). In a multicentre study [40], mean sal-T concentrations from the same 100 males ranged from 240 ± 95 to 410 ± 191 pmol · L − 1 (69-118 pg · ml − 1 ) suggesting considerable heterogeneity between laboratories.…”
Section: Strength Of Evidence and Recommendationsmentioning
confidence: 99%
“…However, the results of this study again indicated that resistance training only acutely affects cortisol, with no long-term circadian rhythm alterations. Similarly, J. Ghigiarelli et al [5] examined the effect of multi-joint, large muscle group, heavy resistance training on athletes' testosterone concentrations. Again, this study demonstrated increased testosterone concentration immediately following resistance training, without long-term alterations.…”
mentioning
confidence: 99%